2017
DOI: 10.1097/md.0000000000007422
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term outcomes of concomitant chemoradiotherapy with temozolomide for newly diagnosed glioblastoma patients

Abstract: The present study analyzed outcomes of surgery followed by concomitant chemoradiotherapy (CCRT) with temozolomide (TMZ) in patients with newly diagnosed glioblastoma (GBM) at a single institution. Outcomes were retrospectively reviewed in 252 consecutive patients with newly diagnosed GBM who underwent surgery followed by CCRT with TMZ at the authors’ institution between 2005 and 2013. At initial operation, 126 (50.0%), 55 (21.8%), 45 (17.9%), and 26 (10.3%) patients underwent gross total resection (GTR), subto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
1
35
1
Order By: Relevance
“…1 Despite multimodal interventions, GBM is associated with a dismal prognosis and a high recurrence rate, which necessitate the development of novel therapeutic approaches. 2,3 However, recent studies targeting angiogenic pathways 4 and cell-matrix interactions 5 have failed to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite multimodal interventions, GBM is associated with a dismal prognosis and a high recurrence rate, which necessitate the development of novel therapeutic approaches. 2,3 However, recent studies targeting angiogenic pathways 4 and cell-matrix interactions 5 have failed to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…An epiphany came from the experience of 5-aminolevulinic acid (5-ALA) fluorescence without any tumor cells in the tumor specimen by pathologic examinations 45) . During surgery to remove GBM, high fluorescence of 5-ALA was found in the walls of ventricles 45) , which are non-coincidentally exposed after supra-total resection (or a so-called planned lobectomy) 52,53) . Moon et al 45) described interesting patterns of 5-ALA fluorescence in the ventricular wall of brain tumor patients.…”
Section: History : Progress Toward the Stem Cell Origin Of Gbmmentioning
confidence: 99%
“…Isocitrate dehydrogenase (IDH)-wildtype glioblastoma (GBM) is a disease with a dismal prognosis, a distinction that has led to GBM being dubbed the "emperor of all cancers". The disease progression is rapid, and even with standard therapy 53) and supra-total resection 52) , the median survival of patients from diagnosis is approximately 14-20 months 53,63) .…”
Section: Introductionmentioning
confidence: 99%
“…Of the 541 publications screened, 23 publications were reviewed in full text based on their relevance, as indicated by title and abstract, and seven publications were selected for a detailed review based on the time horizon and suitability of reported results. All seven publications indicated that the probability of surviving GBM increased the longer patients survived since diagnosis, and that the first 2 years after diagnosis were the period of the highest mortality hazard rates 6,7,[20][21][22][23][24] . We excluded four publications based on single institution reports in favor of larger epidemiological populations 6,[22][23][24] .…”
Section: Epidemiology Datamentioning
confidence: 99%